2017
DOI: 10.1523/jneurosci.3430-13.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Regulatory Mechanisms for the SoxC Transcriptional Network Required for Visual Pathway Development

Abstract: What pathways specify retinal ganglion cell (RGC) fate in the developing retina? Here we report on mechanisms by which a molecular pathway involving Sox4/Sox11 is required for RGC differentiation and for optic nerve formation in mice , and is sufficient to differentiate human induced pluripotent stem cells into electrophysiologically active RGCs. These data place Sox4 downstream of RE1 silencing transcription factor in regulating RGC fate, and further describe a newly identified, Sox4-regulated site for post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 62 publications
6
43
0
Order By: Relevance
“…We propose that the SoxC family of transcription factors, including Sox4 and Sox11, fulfill this role ( Figure 10). This is based on previous reports that deletion of the SoxC genes leads to severely compromised RGC production [97][98][99] , and our finding that they are expressed at high levels in the transitional RPCs and that their expression is not dependent on Atoh7. The SoxC factors likely also function in differentiating RGCs and other cell types, as they continue to be expressed in fate-committed retinal neurons.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We propose that the SoxC family of transcription factors, including Sox4 and Sox11, fulfill this role ( Figure 10). This is based on previous reports that deletion of the SoxC genes leads to severely compromised RGC production [97][98][99] , and our finding that they are expressed at high levels in the transitional RPCs and that their expression is not dependent on Atoh7. The SoxC factors likely also function in differentiating RGCs and other cell types, as they continue to be expressed in fate-committed retinal neurons.…”
Section: Discussionsupporting
confidence: 60%
“…The scRNA-seq data also clarified contradicting results on two genes critical in retinal development. Sox4 and Sox11, which encodes two transcription factors critical for RGC development [97][98][99] , have been identified to be expressed mostly in RGCs, but there have been conflicting reports regarding whether they are also expressed in RPCs 59,[98][99][100] . In the Atoh7-null retina, since most RGCs are absent, it was indicated that Sox4 and Sox11 were downregulated 59,98 .…”
Section: Characteristics Of Individual Cell States During Retinal Devmentioning
confidence: 99%
“…Our results suggest Sox11 is one such critical factor. Both Sox11 and Sox4 are members of the Sry-related high mobility group (HMG) box (SOX) family of transcription factors which have been implicated as critical regulators of cell fate, differentiation, and survival during development (Sarkar and Hochedlinger, 2013; Chang et al, 2017; Kuwajima et al, 2017). Sox11 promoted strong and significant axonal regeneration, and Sox4 likely promoted regeneration albeit with marginal significance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggests that SOX11 activity may be controlled not only by epigenetic and transcriptional mechanisms, but also by post-translational modifications. In retinal ganglion cells, SOX11’s subcellular localization is modulated by SUMOylation 10 . In previous work we identified ten candidate serine residues for phosphorylation via mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%